Evaluation of a leadership program for First Nations, Métis, and Inuit Youth: Stories of positive youth development and community engagement. Issue 2 (3rd April 2018) - Halsall, Tanya; Forneris, Tanya
ABSTRACT: First Nations, Métis, and Inuit (FNMI) youth experience many health disparities in comparison with their mainstream Canadian peers. Researchers have recommended that interventions developed to enhance health and well-being for FNMI youth apply a strengths-based approach that acknowledges contextual challenges. This article uses a qualitative approach to examine the perceived impacts of a program designed to enhance positive development and leadership in FNMI youth. Semistructured interviews were conducted with front-line staff and participants. A thematic data analysis resulted in three major themes that describe the perceived program effects at the participant, staff, and community levels. Findings are discussed in relation to current research and theory, and recommendations are provided for programming and future research. Leadership programming for FNMI youth may be an effective way to promote development across many levels of stakeholders.